Fracture rates by medication type in attention-deficit/hyperactive disorder - Sidrak, Jason P.; Blaakman, Syler R.; Hale, Elijah W. (Frontiers in Surgery, 2023)
Background: ADHD is a condition with extensively researched increased risks of psychiatric disorders, traumatic injury, impulsivity, and delayed response times. Objectives: To analyze the incidences of fractures in patients with ADHD on various medication regimens. Methods: Using the TriNetX database, we created seven patient cohorts, all of age under 25, based on medication types commonly used for ADHD. The cohorts we created were: no medication use, exclusive use of a -phenidate class stimulant, exclusive use of an amphetamine class stimulant, nonexclusive use of formations of either stimulant, exclusive use of non-stimulant medications approved for ADHD, nonexclusive use, and no medications. We then examined rates while controlling for age, sex, race, and ethnicity. Results: The comparison of ADHD to neurotypical individuals revealed an increased risk for all fracture types. For the controlled analysis, all but one cohort had significant differences in each fracture type compared to the baseline cohort of ADHD patients without any medication use. Patients in the “phenidate” cohort had an insignificant difference in risk of lower limb fractures. Patients in the “any medication,” “-etamine,” “stimulant,” and “not ADHD” groups all had significant decreased risks for all fracture types, with confidence intervals often overlapping between treatment modalities. Conclusions: As patients experiment with different medication regimens, providers should be aware of the difference in risk of fracture by medication type. Our results highlight the need for continued research to better discern appropriate medication regimens with the goal of improving overall risk reduction and producing better outcomes for individuals with ADHD.